1997
DOI: 10.1007/s001340050325
|View full text |Cite
|
Sign up to set email alerts
|

A model of gastric emptying using paracetamol absorption in intensive care patients

Abstract: The results suggest that there is a wide range in gastric emptying in critically ill patients. The results may be due to the case mix of the patients. The use of dopamine may adversely affect gastric emptying and requires further investigation in the ICU patient. Prediction of gastric emptying is difficult in these patients and further investigation is necessary in order to improve our understanding of this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(101 citation statements)
references
References 22 publications
4
93
1
3
Order By: Relevance
“…Gastric emptying was assessed by the acetaminophen absorption model. [26][27][28][29] Immediately before administering each study drug or the placebo, 1000 mg of enteral acetaminophen (Zenith Goldline Laboratories, Ft. Lauderdale, FL) as 31.25 mL of solution (32 mg/mL) was administered followed by 10 mL of sterile water. Arterial blood samples of 3 mL were taken from an indwelling catheter at baseline and seven additional times between 30 mins and 720 mins to determine serum acetaminophen concentrations.…”
Section: !mentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric emptying was assessed by the acetaminophen absorption model. [26][27][28][29] Immediately before administering each study drug or the placebo, 1000 mg of enteral acetaminophen (Zenith Goldline Laboratories, Ft. Lauderdale, FL) as 31.25 mL of solution (32 mg/mL) was administered followed by 10 mL of sterile water. Arterial blood samples of 3 mL were taken from an indwelling catheter at baseline and seven additional times between 30 mins and 720 mins to determine serum acetaminophen concentrations.…”
Section: !mentioning
confidence: 99%
“…39 We evaluated gastric emptying with the acetaminophen absorption model. Studies in healthy, 26,40 diabetic, 27 hospitalized, 28 and critically ill 29 subjects have demonstrated that acetaminophen absorption is significantly correlated with gastric emptying. This model has been used in other studies to assess gastric emptying in subsets of critically ill patients 41,42 and studies evaluating prokinetic agents.…”
mentioning
confidence: 99%
“…Tarling and co-workers found sub-therapeutic plasma levels of enterally administered paracetamol, and showed that gastric emptying time varied significantly between patients. [5] Patients in the ICU often have increased vascular permeability secondary to cytokine release, as well as hypo-albuminaemia, which alter the volume of distribution. [6] Furthermore, drug metabolism and excretion may be profoundly affected by hepatic and renal dysfunction.…”
mentioning
confidence: 99%
“…Gastric emptying GE was estimated using the Paracetamol absorption technique (Tarling et al, 1997), as Paracetamol is not absorbed in the stomach, but it rapidly enters the blood stream from the small intestine (Rawlins et al, 1997). Soluble Paracetamol (1.5 g) was dissolved in 100 ml water and given half way through the meal.…”
Section: Nutritional Contentmentioning
confidence: 99%